Frequency of strains with multiple antibiotic resistance in the structure of opportunitistic pathogens - N. M. Voropaeva; U. M. Nemchenko; K. O. Sitnikova; E. D. Savilov; N. N. Chemezova; E. V. Grigorova; A. V. Sorokina; R. E. Zugeeva; N. L. Belkova (Acta Biomedica Scientifica)
Background. The problem of antibiotic resistance has remained significant for the medical community for more than half a century, since the first cases of resistance to penicillin were registered.   The aim. Analysis of the long-term dynamics of changes in the antibacterial resistance of microorganisms and the creation of a collection of multi-resistant strains of opportunistic microorganisms.   Materials and methods. The study included data from 3173 bacteriological samples of various loci of the human body for 2010 and 2020–2021. The sensitivity of isolated cultures was determined by the disk diffusion method to antimicrobial drugs of the following groups: penicillins, cephalosporins, fluoroquinolones, aminoglycosides, carbapenems, tetracyclines, macrolides, lincosamides, oxazolidinones, glycopeptides and others.   Results. In the general structure of conditionally pathogenic microorganisms, a significant increase in the frequency of isolation of multidrug-resistant representatives of the genus Staphylococcus by two or more times was observed in 2021 compared to 2010 and 2020. We also observed a significant increase in the proportion of multidrug-resistant Streptococcus spp. and non-fermenting gram-negative bacteria. These changes marked the beginning of the creation of a collection of conditionally pathogenic microorganisms with multiple antibacterial resistance. In the structure of multiresistant microorganisms included in the “Collection of human microbiota of the Irkutsk region”, the leading positions belong to Klebsiella pneumoniae (23.81 %), Escherichia coli (19.05 %) and Staphylococcus aureus (22.22 %).   Conclusion. Antibiotic resistance monitoring is an important measure to control the resistance of community-acquired and nosocomial (nosocomial) microorganisms both within a particular country and globally.